Unlocking the Potential of Industry 5.0: Increased Productivity, Customization, and Sustainability - Akash Tomar; P.N Ahirwar (International Journal of Advanced Robotics and Automation Technology, 2024)
Building on the tenet of Industry 4.0, Industry 5.0 signifies a paradigm shift in manufacturing and processes in industry while bringing fresh approaches for sustainable production and human-machine interactions. This paper examines the technological drivers, potential benefits, and challenges associated with implementing Industry 5.0 frameworks. Through analysis of current literature and emerging case studies, we explore how advanced technologies such as artificial intelligence, robotics, and the Internet of Things are being integrated to create more adaptive, efficient, and environmentally conscious manufacturing systems. The research highlights the importance of human-centric design, mass customization capabilities, and circular economy principles in shaping the future of industrial production. While significant opportunities exist for increased productivity and sustainability, organizations must address various challenges including technological infrastructure, workforce development, and ethical considerations to successfully transition to Industry 5.0.
Keywords: Industry 5.0; artificial intelligence; fourth industrial revolution; human-robot collaboration; industrial internet of things; smart manufacturing